Light intensity and temperature dependence on performance of a photoelectrochemical cells of ITO/TiO2/PVC-LiClO4/graphite - Rahman M.Y.A.; Salleh M.M.; Talib I.A.; Yahaya M. (2023)
The photovoltaic characteristics of a photoelectrochemical cell of ITO/TiO2/PVC-LiClO4/graphite are reported. This paper is concerned with the influence of light intensity and temperature on short-circuit current density, Jsc and open-circuit voltage, Voc of the device. The photoelectrochemical cell material was a screen-printed layer of titanium dioxide onto an ITO-covered glass substrate, which was used as a working electrode of the cell. The solid electrolyte was polivinylchloride- lithium perchlorate. The graphite film serves as a counter electrode of the cell. The current density-voltage characteristics of the device under an illumination of 20, 40, 60, 80 and 100 mW cm-2 light from a tungsten halogen lamp were recorded at 40 C as well as under an illumination of 100 mW cm-2 at 30, 35, 40, 45 and 50 C, respectively. It was found that the short-circuit current density, Jsc of the device increases with both light intensity and temperature. The Jsc obtained at 100 mW cm-2 was 1.0 ?Acm-2 and that at 50 C was 0.7 ?Acm-2. 2007 Springer-Verlag.